2012
DOI: 10.2106/jbjs.k.01300
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results After Distal Rectus Femoris Transfer as a Part of Multilevel Surgery for the Correction of Stiff-Knee Gait in Spastic Diplegic Cerebral Palsy

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 28 publications
1
44
0
3
Order By: Relevance
“…There are numerous reports regarding the treatment of stiff knee gait using DRFT or proximal rectus femoris release [1,4,6,8,11,18,20,21,23,27,30,32,33,35,38]. Good initial results were reported [1,4,8,11,20,21,23,27,32,33,38].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There are numerous reports regarding the treatment of stiff knee gait using DRFT or proximal rectus femoris release [1,4,6,8,11,18,20,21,23,27,30,32,33,35,38]. Good initial results were reported [1,4,8,11,20,21,23,27,32,33,38].…”
Section: Discussionmentioning
confidence: 99%
“…Good initial results were reported [1,4,8,11,20,21,23,27,32,33,38]. However, some authors have reported discrepant outcomes after DRFT [6,18,30,35], and a poor or no response rate of approximately 20% was found in a recent long-term investigation [6]. These inconsistent outcomes may be explained by a persistent extensor moment of the rectus femoris after transfer [2,3,28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations